Network Diffusion Under Homophily and Consolidation as a Mechanism for Social Inequality. (August 2021) - Zhao, Linda; Garip, Filiz
Network externalities (where the value of a practice is a function of network alters that have already adopted the practice) are mechanisms that exacerbate social inequality under the condition of homophily (where advantaged individuals poised to be primary adopters are socially connected to other advantaged individuals). In their 2011 article, Dimaggio and Garip use an agent-based model of diffusion on a real-life population for empirical illustration and, thus, do not consider consolidation (correlation between traits), a population parameter that shapes network structure and diffusion. Using an agent-based model, this article shows that prior findings linking homophily to segregated social ties and to differential diffusion outcomes are contingent on high levels of consolidation. Homophily, under low consolidation, is not sufficient to exacerbate existing differences in adoption probabilities across groups and can even end up alleviating intergroup inequality by facilitating diffusion.